Alih Ekonomi Masyarakat Di Desa Pangauban Melalui Inovasi Produk - Fransisca, Yuniati; Christianingsih, Endah; Rukmana, Asep R. (Universitas Nusantara PGRI Kediri, 2020)
The Citarum River was ranked as the 3rd most dirtiest river in the world. Troubleshooting Citarum River requires the handling and support of programs involving various parties. KKNM Thematic Citarum Harum is one of the support of the Ministry of Research, Technology and higher education that facilitates the participation of academic students in creating innovations for the Citarum watershed control. The implementation of KKNM as a vehicle for community service is expected to develop students ' practical skills in absorbing the skills in the campus that are then transformed in the community. Nurtanio University Bandung is part of the program